Preparation method and application of nitrogen-carbon porous material based on bimetallic ZIFs
Through the preparation method of nitrogen-carbon porous material based on bimetallic ZIFs, the problem of insufficient performance of traditional graphite negative electrode materials is solved, and a nitrogen-carbon porous negative electrode material with high specific capacity, excellent cycle stability and good rate performance is achieved, which significantly improves the performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202510056601.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The theoretical specific capacity of traditional graphite negative electrode materials is relatively low, which is difficult to meet the needs of high-performance lithium-ion batteries, especially in terms of high specific capacity, long cycle life and good rate performance.
Using the preparation method of nitrogen-carbon porous materials based on bimetallic ZIFs, a bimetallic zeolite imidazole ester frame material is generated by solvothermal synthesis method, and pyrolytic carbonization is performed to obtain nitrogen-doped porous carbon material with rich multi-stage porous structure and high specific capacity.
The prepared nitrogen-carbon porous anode material has high specific capacity (up to 750mAh/g), excellent cycle stability and good rate performance. It can still maintain a high capacity retention rate (up to 98.7%) after multiple charge and discharge cycles, significantly improving the performance of lithium-ion batteries.
Smart Images

Figure CN119841302A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of synthesis and preparation of negative electrode materials for lithium ion batteries, and in particular to a preparation method and application of a nitrogen-carbon porous material based on bimetallic ZIFs. Background Art
[0002] With the rapid development of portable electronic devices, electric vehicles and other fields, the requirements for the performance of lithium-ion batteries are increasing. As a key component of lithium-ion batteries, the performance of negative electrode materials directly affects important indicators such as battery energy density, charge and discharge efficiency, and cycle life. The theoretical specific capacity of traditional graphite negative electrode materials is relatively low (theoretical specific capacity is about 372mAh / g), which is difficult to meet the needs of high-performance lithium-ion batteries. Therefore, the development of new negative electrode materials with high capacity, long cycle life and good rate performance has become a current research hotspot.
[0003] In the existing technology, nitrogen-carbon porous materials have shown great potential in lithium-ion battery applications due to their unique porous structure, high conductivity, and good chemical stability. Zeolite imidazolate framework (ZIFs) materials have highly ordered crystal structures, rich pore structures, and adjustable metal centers, making them ideal precursors for preparing nitrogen-doped porous carbon. By introducing bimetallic centers into the ZIFs structure, the electronic structure and pore characteristics of the material can be further regulated, thereby optimizing its performance as a negative electrode material for lithium-ion batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a nitrogen-carbon porous material based on bimetallic ZIFs. The prepared negative electrode material has high specific capacity, excellent cycle stability and good rate performance, and shows good application prospects in the field of lithium-ion batteries.
[0005] To achieve the above object, the present invention provides a method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs, comprising the following steps:
[0006] S1. Dissolve zinc nitrate hexahydrate, cobalt nitrate hexahydrate and an organic ligand in a DMF solution in a molar ratio, stir evenly to obtain a reaction solution, generate a solid product by a solvent thermal synthesis method, and obtain a bimetallic zeolite imidazolate framework powder material by centrifugation, washing and drying;
[0007] S2. Under an inert atmosphere, the bimetallic zeolite imidazolate framework powder material obtained in S1 is subjected to pyrolysis and carbonization treatment, cooled to generate a block product, soaked in a dilute hydrochloric acid solution, filtered, washed with water until neutral, and dried to obtain a nitrogen-carbon porous material.
[0008] Preferably, in S1, the molar ratio of the zinc nitrate hexahydrate to the cobalt nitrate hexahydrate is 1-9:1-9, and the specific molar ratio is one of 9:1, 3:1, 1:1, 1:3, and 1:9.
[0009] Preferably, in S1, the organic ligands are imidazole and benzimidazole, and the molar ratio thereof is 13.5:1.5.
[0010] Preferably, in S1, the solvent thermal synthesis method is specifically:
[0011] The reaction solution is placed in a stainless steel reactor lined with polytetrafluoroethylene and moved into a drying oven. The temperature is 110-130°C and the reaction time is 24-96h. After the reactor is cooled to room temperature with the drying oven, the upper solvent is poured off, washed, and dried to obtain a solid product.
[0012] Preferably, in S2, the pyrolysis carbonization treatment is specifically:
[0013] The bimetallic zeolite imidazolate framework material is placed in a covered quartz boat, transferred to a tubular furnace protected by an inert atmosphere, heated to 600-900°C at a heating rate of 2-5°C / min, and kept at this temperature for 2-4h, and naturally cooled to room temperature to obtain a solid product.
[0014] Preferably, in S2, the dilute hydrochloric acid solution immersion treatment time is 3 to 16 hours.
[0015] To achieve the above object, the present invention also provides an application of a nitrogen-carbon porous material in a negative electrode material of a lithium ion battery.
[0016] Preferably, the preparation method is as follows:
[0017] The nitrogen-carbon porous material, the conductive agent and the binder are mixed evenly in a certain proportion, and then N-methylpyrrolidone solvent is added to make a slurry, and the slurry is evenly coated on the copper foil current collector, and then dried and punched to obtain the negative electrode material of the lithium-ion battery.
[0018] Preferably, the conductive agent is acetylene black, the binder is polyvinylidene fluoride, and the mass ratio of the nitrogen-carbon porous material, acetylene black and polyvinylidene fluoride is 8:1:1 or 7:2:1.
[0019] Preferably, the slurry is made by ball milling, and the coating thickness of the slurry is 200-400 μm.
[0020] Therefore, the present invention adopts the above-mentioned preparation method of the nitrogen-carbon porous material based on bimetallic ZIFs and its application, and the beneficial effects are as follows:
[0021] (1) The nitrogen-carbon porous material prepared by the present invention uses a bimetallic zeolite imidazolate skeleton as a precursor and utilizes the synergistic effect of the bimetal to effectively regulate the pore structure and electronic structure of the material. The prepared nitrogen-doped porous carbon has a rich and uniformly distributed multi-level pore structure.
[0022] (2) The negative electrode material prepared by the present invention has a high specific capacity. By doping nitrogen atoms, the material is given an additional pseudocapacitive effect, which significantly improves the specific capacity of the material. Compared with traditional graphite negative electrode materials, the specific capacity is greatly improved and can reach 750 mAh / g.
[0023] (3) The nitrogen-carbon porous negative electrode material prepared by the present invention has good rate performance and excellent cycle stability. Its rich and evenly distributed multi-level pore structure is conducive to the rapid transmission and storage of lithium ions. It can still maintain a high capacity retention rate after multiple charge and discharge cycles. After 100 cycles, the capacity retention rate can reach 98.7%, showing good application prospects in the field of lithium-ion batteries.
[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of a nitrogen-carbon porous material in Example 1 of a method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs of the present invention;
[0026] Figure 2 The powder XRD diagrams of the nitrogen-carbon porous materials of Examples 1 to 5 of the preparation method of the nitrogen-carbon porous material based on bimetallic ZIFs of the present invention;
[0027] Figure 3 It is a charge-discharge cycle diagram of application examples 6 to 7 of a nitrogen-carbon porous material based on bimetallic ZIFs of the present invention;
[0028] Figure 4 These are rate diagrams of application examples 6 and 7 of a nitrogen-carbon porous material based on bimetallic ZIFs of the present invention. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0030] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0031] Embodiment 1
[0032] A method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs comprises the following steps:
[0033] (1) Zinc nitrate hexahydrate and cobalt nitrate hexahydrate were weighed in a molar ratio of 9:1, imidazole and benzimidazole were selected as organic ligands, and they were dissolved in DMF solution. The three solvents were mixed and stirred for about 30 minutes and then transferred to a 100 ml stainless steel reactor lined with polytetrafluoroethylene. The reactor was moved into an electric heated blast drying oven and kept at a constant temperature of 130°C for 96 hours. After the reactor was cooled to room temperature with the drying oven, the upper layer of solvent was poured out, the product was taken out with a spatula, and the precipitate was collected by centrifugation, washed with DMF 3 times, and then the sample was dried in a vacuum drying oven at a temperature of 110°C for 12 hours. The bimetallic zeolite imidazolate framework (ZIFs) powder was obtained.
[0034] (2) The obtained bimetallic zeolite imidazolate framework (ZIFs) powder is placed in a covered quartz boat, and then transferred to a tube furnace under inert gas protection, and heated to 600°C at a heating rate of 5°C / min, and kept at this temperature for 2 hours for pyrolysis and carbonization. After the pyrolysis and carbonization is completed, it is naturally cooled to room temperature, and the obtained block product is taken out and soaked in a dilute hydrochloric acid solution for 6 hours to remove possible residual metal impurities as much as possible, and then filtered and washed with water to neutrality, and then placed in a vacuum drying oven again, and dried at 100°C for 24 hours to obtain a nitrogen-carbon porous material.
[0035] Embodiment 2
[0036] A method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs comprises the following steps:
[0037] (1) Zinc nitrate hexahydrate and cobalt nitrate hexahydrate were weighed in a molar ratio of 3:1, imidazole and benzimidazole were selected as organic ligands, and they were dissolved in DMF solution. The four solvents were mixed and stirred for about 30 minutes and then transferred to a 100 ml stainless steel reactor lined with polytetrafluoroethylene. The reactor was moved into an electric heated forced air drying oven (120°C) and kept warm for 96 hours. After the reactor was cooled to room temperature with the drying oven, the upper solvent was poured out, the product was taken out with a spatula, and the precipitate was collected by centrifugation, washed with DMF 3 times, and then the sample was dried in a vacuum drying oven at 110°C for 12 hours. Bimetallic zeolite imidazolate framework (ZIFs) powder was obtained.
[0038] (2) The obtained bimetallic zeolite imidazolate framework (ZIFs) powder is placed in a covered quartz boat, and then transferred to a tube furnace under inert gas protection, and heated to 700°C at a heating rate of 5°C / min, and kept at this temperature for 2 hours for pyrolysis and carbonization. After the pyrolysis and carbonization is completed, it is naturally cooled to room temperature, and the obtained block product is taken out and soaked in a dilute hydrochloric acid solution for 16 hours to remove possible residual metal impurities as much as possible, and then filtered and washed with water to neutrality, and then placed in a vacuum drying oven again, and dried at 100°C for 24 hours to obtain a nitrogen-carbon porous material.
[0039] Embodiment 3
[0040] A method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs comprises the following steps:
[0041] (1) Zinc nitrate hexahydrate and cobalt nitrate hexahydrate were weighed in a molar ratio of 1:1, imidazole and benzimidazole were selected as organic ligands, and they were dissolved in DMF solution. The four solvents were mixed and stirred for about 30 minutes and then transferred to a 100 ml stainless steel reactor lined with polytetrafluoroethylene. The reactor was moved into an electric heated blast drying oven and kept at a constant temperature of 130°C for 48 hours. After the reactor was cooled to room temperature with the drying oven, the upper solvent was poured out, the product was taken out with a spatula, and the precipitate was collected by centrifugation, washed with DMF 3 times, and then the sample was dried in a vacuum drying oven at a temperature of 110°C for 12 hours. The bimetallic zeolite imidazolate framework (ZIFs) powder was obtained.
[0042] (2) The obtained bimetallic zeolite imidazolate framework (ZIFs) powder is placed in a covered quartz boat, transferred to a tube furnace, and heated to 800°C at a heating rate of 5°C / min under inert gas protection, and kept at this temperature for 3 hours for pyrolysis and carbonization. After the pyrolysis and carbonization is completed, it is naturally cooled to room temperature, and the obtained block product is taken out and soaked in a dilute hydrochloric acid solution for 10 hours to remove possible residual metal impurities as much as possible, and then filtered and washed with water to neutrality, and then placed in a vacuum drying oven again, and dried at 100°C for 24 hours to obtain a nitrogen-carbon porous material.
[0043] Embodiment 4
[0044] A method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs comprises the following steps:
[0045] (1) Zinc nitrate hexahydrate and cobalt nitrate hexahydrate were weighed in a molar ratio of 1:3, imidazole and benzimidazole were selected as organic ligands, and they were dissolved in DMF solution. The four solvents were mixed and stirred for about 30 minutes and then transferred to a 100 ml stainless steel reactor lined with polytetrafluoroethylene. The reactor was moved into an electric heated forced air drying oven and kept at 130°C for 96 hours. After the reactor was cooled to room temperature with the drying oven, the upper solvent was poured out, the product was taken out with a spatula, and the precipitate was collected by centrifugation, washed with DMF 3 times, and then the sample was dried in a vacuum drying oven at 110°C for 12 hours. The bimetallic zeolite imidazolate framework (ZIFs) powder was obtained.
[0046] (2) The obtained bimetallic zeolite imidazolate framework (ZIFs) powder is placed in a covered quartz boat, transferred to a tube furnace, and heated to 900°C at a heating rate of 5°C / min under inert gas protection, and kept at this temperature for 2 hours for pyrolysis and carbonization. After the pyrolysis and carbonization is completed, it is naturally cooled to room temperature, and the obtained block product is taken out and soaked in a dilute hydrochloric acid solution for 3 hours to remove possible residual metal impurities as much as possible, and then filtered and washed with water to neutrality, and then placed in a vacuum drying oven again, and dried at 100°C for 24 hours to obtain a nitrogen-carbon porous material.
[0047] Embodiment 5
[0048] A method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs comprises the following steps:
[0049] (1) Zinc nitrate hexahydrate and cobalt nitrate hexahydrate were weighed in a molar ratio of 1:9, imidazole and benzimidazole were selected as organic ligands, and they were dissolved in DMF solution. The four solvents were mixed and stirred for about 30 minutes and then transferred to a 100 ml stainless steel reactor lined with polytetrafluoroethylene. The reactor was moved into an electric heated forced air drying oven and kept at a constant temperature of 110°C for 96 hours. After the reactor was cooled to room temperature with the drying oven, the upper solvent was poured out, the product was taken out with a spatula, and the precipitate was collected by centrifugation, washed with DMF 3 times, and then the sample was dried in a vacuum drying oven at a temperature of 110°C for 12 hours. The bimetallic zeolite imidazolate framework (ZIFs) powder was obtained.
[0050] (2) The obtained bimetallic zeolite imidazolate framework (ZIFs) powder is placed in a covered quartz boat, transferred to a tube furnace, and heated to 800°C at a heating rate of 5°C / min under the protection of inert gas, and kept at this temperature for 2 hours for pyrolysis and carbonization. After the pyrolysis and carbonization is completed, it is naturally cooled to room temperature, and the obtained block product is taken out and soaked in a dilute hydrochloric acid solution for 10 hours to remove possible residual metal impurities as much as possible, and then filtered and washed with water to neutrality, and then placed in a vacuum drying oven again, and dried at 100°C for 24 hours to obtain a nitrogen-carbon porous material.
[0051] Embodiment 6
[0052] The nitrogen-carbon porous material prepared in Example 1, the conductive agent (acetylene black) and the binder (polyvinylidene fluoride, PVDF) were mixed uniformly in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added, and ball milled for 4 hours to prepare a uniform slurry. The slurry was evenly coated on the copper foil current collector, and the coating thickness was controlled to be 200 μm. Then, the coated copper foil was placed in a vacuum drying oven and dried at 100°C for 24 hours. After drying, it was punched into a circle by a punching machine as a negative electrode material for a lithium-ion battery.
[0053] Embodiment 7
[0054] The nitrogen-carbon porous material prepared in Example 3, the conductive agent (acetylene black) and the binder (polyvinylidene fluoride, PVDF) were mixed uniformly in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added, and the mixture was ball-milled for 4 hours to form a uniform slurry. The slurry was evenly coated on the copper foil current collector, and the coating thickness was controlled to be 200 μm. The coated copper foil was then placed in a vacuum drying oven and dried at 100°C for 24 hours. After drying, it was punched into a circular shape by a punching machine as a negative electrode material for a lithium-ion battery.
[0055] Experimental Testing
[0056] The nitrogen-carbon porous materials prepared in Examples 1 to 5 were subjected to SEM structural analysis. The SEM results of the sample obtained in Example 1 are as follows: Figure 1 As shown in Figure 2, it can be clearly seen that the material has a porous structure and contains a small amount of carbon nanotubes.
[0057] The bimetallic zeolite imidazolate frameworks (ZIFs) prepared in Examples 1 to 5 were subjected to XRD analysis. The results are as follows: Figure 2 As shown. It can be seen that the spectrum of the synthetic material is similar to the standard ZIF-62 spectrum Figure 1 The results of the charge and discharge cycles are shown in Figure 2. Figure 3 As shown, the magnification results are as follows Figure 4 shown.
[0058] At a charge and discharge voltage of 0.01-3.0V and 0.1A·g -1 The cycle performance test was carried out at a current density of 763.5 mA·h·g -1 After 100 cycles, the specific capacity is 753.8 mA·h·g -1 , with a high capacity and a capacity retention rate of up to 98.7%, which can still maintain a high capacity retention rate after multiple charge and discharge cycles. At current densities of 0.1, 0.2, 0.5, 1, 2, and 5A·g-1, the reversible capacities are 887.2, 676.2, 534.8, 570.7, 454.5, and 380.2 mA·h·g-1, respectively. -1 When the current density returns to 0.1A·g -1 When 62-(Zn:Co=1:1) obtains 700.3mA·h·g -1Therefore, the present invention adopts the above-mentioned preparation method of the nitrogen-carbon porous material based on bimetallic ZIFs and its application, and the prepared negative electrode material has high specific capacity, excellent cycle stability and good rate performance, showing good application prospects in the field of lithium-ion batteries.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs, characterized in that: The following steps are involved: S1. Dissolve zinc nitrate hexahydrate, cobalt nitrate hexahydrate and an organic ligand in a DMF solution in a molar ratio, stir evenly to obtain a reaction solution, generate a solid product by a solvent thermal synthesis method, and obtain a bimetallic zeolite imidazolate framework powder material by centrifugation, washing and drying; S2. Under an inert atmosphere, the bimetallic zeolite imidazolate framework powder material obtained in S1 is subjected to pyrolysis and carbonization treatment, cooled to generate a block product, soaked in a dilute hydrochloric acid solution, filtered, washed with water until neutral, and dried to obtain a nitrogen-carbon porous material.
2. The method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs according to claim 1, characterized in that: In S1, the molar ratio of the zinc nitrate hexahydrate to the cobalt nitrate hexahydrate is 1-9:1-9.
3. The method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs according to claim 1, characterized in that: In S1, the organic ligands are imidazole and benzimidazole, and the molar ratio of imidazole to benzimidazole is 13.5:1.
5.
4. The method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs according to claim 1, characterized in that: In S1, the solvent thermal synthesis method is specifically: The reaction solution is placed in a stainless steel reactor lined with polytetrafluoroethylene and moved into a drying oven. The temperature is 110-130°C and the reaction time is 24-96h. After the reactor is cooled to room temperature with the drying oven, the upper solvent is poured off, washed, and dried to obtain a solid product.
5. The preparation method of a nitrogen-carbon porous material based on bimetallic ZIFs and its application according to claim 1, characterized in that: In S2, the pyrolysis carbonization treatment is specifically: The bimetallic zeolite imidazolate framework powder material is placed in a covered quartz boat, transferred to a tube furnace protected by an inert atmosphere, heated to 600-900°C at a heating rate of 2-5°C / min, and kept at this temperature for 2-4h, and naturally cooled to room temperature to obtain a solid product.
6. The method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs according to claim 1, characterized in that: In S2, the dilute hydrochloric acid solution immersion treatment time is 3 to 16 hours.
7. Application of a nitrogen-carbon porous material prepared by the method for preparing a nitrogen-carbon porous material based on bimetallic ZIFs as described in any one of claims 1 to 6 in a negative electrode material for a lithium-ion battery.
8. The use of a nitrogen-carbon porous material in a negative electrode material for a lithium-ion battery according to claim 7, characterized in that: The preparation method is as follows: The nitrogen-carbon porous material, the conductive agent and the binder are mixed evenly in a certain proportion, and then N-methylpyrrolidone solvent is added to make a slurry, and the slurry is evenly coated on the copper foil current collector, and then dried and punched to obtain the negative electrode material of the lithium-ion battery.
9. The use of a nitrogen-carbon porous material in a negative electrode material for a lithium-ion battery according to claim 8, characterized in that: The conductive agent is acetylene black, the binder is polyvinylidene fluoride, and the mass ratio of the nitrogen-carbon porous material, acetylene black and polyvinylidene fluoride is 8:1:1 or 7:2:
1.
10. The preparation method of a nitrogen-carbon porous material based on bimetallic ZIFs and its application according to claim 8, characterized in that: The slurry is prepared by ball milling, and the coating thickness of the slurry is 200-400 μm.
Citation Information
Patent Citations
Preparation method and application of graded porous carbon material
CN105384161A
Metal-nitrogen doped porous carbon material and preparation method and application thereof
CN113675402A
Preparation method of nitrogen-doped dendritic porous carbon nanotube
CN114057183A
Preparation and application of hydrangea-shaped ZIFs complex mediated bimetallic nitrogen carbon material
CN118553925A